Fleas of Shrews and Rodents in Rural Lowland Taiwan. Issue 2 (2nd November 2019) - Wang, Hsi-Chieh; Lee, Pei-Lung; Kuo, Chi-Chien
Abstract: Fleas transmit a variety of pathogens to humans but are relatively understudied in comparison to mosquitoes and ticks, including in Taiwan, where fleas in rural lowlands have never been systematically surveyed. In total, 700 fleas of four species were collected from 1, 260 shrews and rodents at nine counties across lowland Taiwan. Nosopsyllus nicanus Jordan (Siphonaptera: Ceratophyllidae) and Xenopsylla cheopis Rothschild (Siphonaptera: Pulicidae) were the most abundant flea species (79.0 and 14.6% of total fleas, respectively); the former was largely limited to the islets, while the latter was restricted to the Taiwan main island. Rattus losea Swinhoe (Rodentia: Muridae) was the most common small mammal species (49.3% of total) and hosted the majority of fleas (88.3% of total). Five Rickettsia spp., including Rickettsia conorii Brumpt (Rickettsiales: Rickettsiaceae), Rickettsia felis Bouyer et al. Rickettsia japonica Uchida, Rickettsia raoultii Mediannikov, and Rickettsia rickettsii Brumpt or closely related species, were identified from 67 individually assayed fleas based on ompB and gltA genes. Rickettsia felis, mainly transmitted by fleas, was detected in one X. cheopis in southern Taiwan where a confirmed human case of infection with R. felis has been reported. The presence of R. felis, along with the other four tick-borne Rickettsia spp., demonstrates that a variety of rickettsiae circulate in rural lowland Taiwan and could pose risks to human health.